Nurse education today: Between teaching and publication focus - Gunawan, Joko; Aungsuroch, Yupin; Fisher, Mary L (Belitung Nursing Journal, 2021)
“Publish or Perish” is no longer an imagination. On the contrary, it is considered a new reality in nursing education today. All nurse scholars, researchers, faculty members, and students are eager and compete with each other to publish their research works in academic journals. Success in this challenge brings personal benefits, especially for academic reputation and promotion, as well as organizational benefits, such as university ranking and sponsorship. However, despite the advantages of faculty publication, the pros and cons of this topic are on the rise. Therefore, this article aims to discuss the publication-related phenomenon in nursing education, followed by concerns and recommendations for consideration.